Global and local shape features of the hippocampus based on Laplace–Beltrami eigenvalues and eigenfunctions: a potential application in the lateralization of temporal lobe epilepsy - Shishegar, Rosita; Gandomkar, Ziba; Fallahi, Alireza; Nazem-Zadeh, Mohammad-Reza; Soltanian-Zadeh, Hamid (Neurological sciences, 2022)
Using magnetic resonance (MR) images to evaluate changes in the shape of the hippocampus has been an active research topic. This paper presents a new shape analysis approach to quantify and visualize deformations of the hippocampus in epilepsy. The proposed method is based on Laplace–Beltrami (LB) eigenvalues and eigenfunctions as isometric invariant shape features, and thus, the procedure does not require any image registration. In addition to the LB-based shape features, total hippocampal volume and surface area are calculated using manually segmented images. Theses shape and volumetric descriptors are used to distinguish the patients with temporal lobe epilepsy (TLE) ( N = 55) from healthy control subjects ( N = 12, age = 32.2 ± 9.1, sex (M/F) = 6/6) and patients with right TLE ( N = 26, age = 45.1 ± 11.0, sex (M/F) = 9/17) from left TLE ( N = 29, age = 45.4 ± 11.9, sex (M/F) = 10/19). Experimental results illustrate the usefulness of the proposed approach for the diagnosis and lateralization of TLE with 93.0% and 86.4% of the cases, respectively. Moreover, the proposed method outperforms the volumetric analysis in terms of both sensitivity (94.9% vs. 88.1%) and specificity (83.3% vs. 50.0%) of the lateralization. The analysis of local hippocampal thickness variations suggests significant deformation in both ipsilateral and contralateral hippocampi of epileptic patients, while there were no differences between right and left hippocampi in controls. It is anticipated that the proposed method could be advantageous in the presurgical evaluation of patients with drug-resistant epilepsy; however, further validation of the method using a larger dataset is required.